Phototherapy in Pediatric Dermatology - Harningtyas, Citra Dwi; Yuri Widia (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Phototherapy is a safe and effective treatment modality for skin diseases in children such as psoriasis, atopic dermatitis, pityriasis lichenoides, vitiligo, cutaneous cell lymphoma, pityriasis rubra pilaris, and other skin disorders. It is reported to be effective with less side effects compare to the administration of systemic medicine. Short and long term side effects should be taken into account when applying this model of therapy, especially in children. Purpose: To identify special considerations regarding the use of phototherapy modalities in the field of dermatology in children. Review: Phototherapy is the use of ultraviolet (UV) radiation for therapeutic purposes. The various wavelengths of UV radiation used for phototherapy have their own respective photochemical and photobiological properties. There are modality choices that have been proven to provide benefits in treating various skin diseases, including broadband UVB and narrowband UVB, psoralen UVA photochemotherapy (PUVA), ultraviolet A 1 (UVA1), and targeting phototherapy. Special considerations regarding the use of this treatment modality in the pediatric population increase with safety and treatment tolerance. Conclusion: Special considerations should be taken when providing phototherapy treatment options to children with skin disorders requiring phototherapy. The therapies are generally well tolerated and mostly have minor adverse side effects, such as sunburn.